Cryptococcus neoformans Virulence Is Enhanced after Growth in the Genetically Malleable Host Dictyostelium discoideum - Steenbergen, Judith N. (American Society for Microbiology, 2003)
Cryptococcus neoformans is an encapsulated, environmental fungus that can cause life-threatening meningitis. Pathogenicity of C. neoformans for macrophages and vertebrate hosts may be a mechanism selected in evolution for protection against environmental predators. In this study, we investigated whether Dictyostelium discoideum could serve as an alternate host for C. neoformans. D. discoideum has a defined genetic system which provides significant advantages for the study of fungus-amoeba interactions. Our results show that D. discoideum is susceptible to infection with C. neoformans and that the interactions are similar to those described previously for this fungus with macrophages and Acanthamoeba castellanii. Acapsular C. neoformans cells did not replicate when coincubated with D. discoideum. However, incubation of acapsular C. neoformans with D. discoideum mutants defective in myosin VII synthesis resulted in infection, validating the concept that avirulent organisms can be virulent in impaired hosts even at the unicellular level. Phagocytosis of C. neoformans by D. discoideum could be inhibited with capsule-specific antibodies and various sugars. Passage of an encapsulated C. neoformans strain through D. discoideum cultures increased virulence and was accompanied by larger capsules and faster time to melanization. These results add to the evidence implicating soil ameboid predators as important factors for the maintenance of C. neoformans virulence in the environment and suggest that D. discoideum promises to be an extremely useful system for studying the interaction of C. neoformans with phagocytic cells.